Spółka miejska w usługach komunalnych - Dominik Gralka (Ekonomiczne Problemy Usług, 2015)
An attempt to scrape the position of the municipal company in the system of providing the public service in the city is contents of the article, as the fundamental unit of the local self-government. City authorities are making choice of the effective form of the own execution of tasks. The council company constitutes is an economic organization closely connected with organs of the city. In the operations of this company a visible contradiction is occurring between represented social objectives through mayor or of president, and with goals of the company as the business entity. The role of the supervisory board has a regulating capacity and relies on the similarity of these purposes, with cost of lowering the effectiveness of action.